PENGARUH PREPARASI DAN BLANCHING TERHADAP MUTU REBUNG IKAN TERFERMENTASI (LEMEA) [The Effect of Preparation and Blanching to Quality of Fermented Bamboo Shoots and Fish (Lemea)] - Zuidar, Ahmad Sapta; Rizal, Samsul; Hadi, Jessica Puteri Octavia (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2019)
Quality is one of the important factors in producing lemea - a fermented bamboo shoots and fish. Objectives of this research were to find out effects of preparation and their interaction to produce the best quality of lamea. This research used randomized complete block design with two factors and three replications. The first factor was preparations (P) consisting of four levels, namely preparation by smoothing and stirring (P1), preparation by cutting and stirring (P2), preparation by smoothing and coating (P3), and preparation by cutting and coating (P4). The second factor was blanching (B) consisting of two levels, namely without blanching (B0) and blanching (B1). In order to determine its quality, lemea was observed for its content of lactic acid bacteria, total volatile nitrogen, moisture content, and protein content as well as its sensory characteristics (color, aroma, texture, and overall acceptability scores). Collected data were analysed for its variances and the results showed that preparation and blanching treatments significantly affected lemea’s total volatile nitrogen and sensory characteristics. The best lemea quality was obtained from combination treatment of blanching with chopped and stirred preparation (B1P2). The lemea had lactic acid bacteria of 10.1160 log cfu/g, total volatile nitrogen of 43.14 mg/100g, moisture content of 87.99% (b/v), color score of 4.34 (yellowish white), aroma score of 3.78 (rot), texture score of 4.53 (soft) and overall acceptance score of 3.90 (likes).